PENGARUH PEMBERIAN JINTAN HITAM (Nigella sativa) TERHADAP KADAR HDL (HIGH DENSITY LIPOPROTEIN) DAN LDL (LOW DENSITY LIPOPROTEIN) PADA BROILER JANTAN - Syahroni Syahroni; Purnama Edy Santosa; Siswanto Siswanto; Madi Hartono (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2021)
These study aimed to determine the effectiveness of Nigella sativa in increasing HDL levels and reducing LDL levels in male broilers. This research was conducted in December 2019 - January 2020 at the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. Analysis of HDL and LDL levels was carried out in Pramitra Biolab Indonesia. The study used sixty blood samples of Cobb male broiler. This study used a completely randomized design (CRD) with four treatments and each treatment was repeated three times, namely drinking water without a mixture of Nigella sativa (P0), drinking water with 36 mg/kg body weight=BW/day Nigella sativa (P1), drinking water with 72 mg/kg BW/day Nigella sativa (P2), drinking water with 144 mg/kg BW/day Nigella sativa (P3). Based on descriptive analysis that has been done Nigella sativa was effective in increasing HDL levels and reducing LDL levels in male broilers. Giving Nigella sativa with dose of 72 mg/kg BW/day resulted in the highest HDL levels of 88.6 mg/dl, whereas administration of Nigella sativa with dose of 144 mg/kg BW/day resulted in the lowest LDL level of 31.3 mg/dl. Keywords: HDL LDL, Male broiler chickens, Nigella sativa